2021
DOI: 10.7554/elife.69314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SARS-CoV-2 proteins on vascular permeability

Abstract: Severe acute respiratory syndrome (SARS)-CoV-2 infection leads to severe disease associated with cytokine storm, vascular dysfunction, coagulation, and progressive lung damage. It affects several vital organs, seemingly through a pathological effect on endothelial cells. The SARS-CoV-2 genome encodes 29 proteins, whose contribution to the disease manifestations, and especially endothelial complications, is unknown. We cloned and expressed 26 of these proteins in human cells and characterized the endothelial re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 86 publications
(89 reference statements)
2
42
0
2
Order By: Relevance
“…Similarly, Feng and colleagues utilized a rhesus macaque model of SARS-CoV-2 respiratory tract infection and observed that SARS-CoV-2 infection significantly reduced VE-cadherin levels in the heart of rhesus macaques when compared to uninfected controls ( 75 ). In agreement with these in vivo observations, several in vitro studies demonstrated that SARS-CoV-2 spike proteins can also disorganize the VE-cadherin complex and decrease VE-cadherin levels in cultured endothelial cells ( 69 , 72 , 74 ). Therefore, SARS-CoV-2 infection can disrupt VE-cadherin largely responsible for the vascular permeability in COVID-19 patients.…”
Section: Aerobic Glycolytic Metabolism and Endothelial Cell Injury In...supporting
confidence: 73%
See 1 more Smart Citation
“…Similarly, Feng and colleagues utilized a rhesus macaque model of SARS-CoV-2 respiratory tract infection and observed that SARS-CoV-2 infection significantly reduced VE-cadherin levels in the heart of rhesus macaques when compared to uninfected controls ( 75 ). In agreement with these in vivo observations, several in vitro studies demonstrated that SARS-CoV-2 spike proteins can also disorganize the VE-cadherin complex and decrease VE-cadherin levels in cultured endothelial cells ( 69 , 72 , 74 ). Therefore, SARS-CoV-2 infection can disrupt VE-cadherin largely responsible for the vascular permeability in COVID-19 patients.…”
Section: Aerobic Glycolytic Metabolism and Endothelial Cell Injury In...supporting
confidence: 73%
“…A previous study shows that integrin α5β1 activates NF-κB in ECs to elicit inflammation ( 73 ). Consistently, SARS-CoV-2 protein treatment enhanced p65 nuclear accumulation and IL-6 expression in ECs ( 72 , 74 ). To explore the mechanism of myocardial injury in COVID-19 infected patients, Feng et al.…”
Section: Endothelial Cell Dysfunction In Covid-19 Infected Patientsmentioning
confidence: 55%
“…Virus uptake occurred, but viral replication was not supported. Another study using HUVECs reported that cloned SARS-CoV-2 proteins cause vascular permeability [159]. Resolving these controversies requires further interrogation using physiological human model systems, including more complex organoid models, where the vasculature is embedded within the organoid.…”
Section: Vasculaturementioning
confidence: 99%
“…We then asked whether inflammation was restricted to parenchymal or meningeal/ventricular compartments. Barrier forming cells of the cerebrovasculature (Krasemann et al ., 2022; Rauti et al, 2021; Reynolds and Mahajan, 2021), meninges, and choroid plexus (Pellegrini et al, 2020; Yang et al, 2021) are potential targets of SARS-CoV-2 infection and demonstrate inflammatory changes in COVID-19 infected individuals and animal models. We therefore measured foci of inflammation in the BBB, blood-meningeal barrier, and blood-cerebral spinal fluid barrier.…”
Section: Resultsmentioning
confidence: 99%